Factors predicting the presence of depression in obstructive sleep apnea - Sheikh Shoib; Soumitra Das (Industrial Psychiatry Journal, 2020)
Background: Obstructive sleep apnea (OSA) is a sleep-related breathing disorder and is associated with a myriad of neurocognitive dysfunctions and cardiac and metabolic diseases. Several studies have shown the relation of depressive symptom in patients with OSA. Keeping this in view, we planned to study various factors predicting the presence of depression in OSA. Aim: The aim of the study was to study various factors predicting the presence of depression in OSA. Methods: We performed polysomnography (PSG) studies on patients that were referred from various subspecialty clinics from July 2011 to August 2013. Psychiatric diagnosis was done using the Mini International Neuropsychiatric Interview (plus) scale. This was followed by the application of the Hamilton Depression Rating Scale. Standard methods of statistical analysis were used for data analysis. All statistical analyses were performed using SPSS software version 11.0 (SPSS, Chicago, Illinois, USA) and tests of statistical significance were two-sided and differences were taken as significant when P-value was less than 0.05. Results: Of 182 patients who underwent PSG, 47 were suffering from depression with a mean age of 58.60 years. Age, gender, snoring, body mass index, hypertension, witnessed apnea, nocturia, disturbed sleep, and daytime sleepiness were significantly correlated with depression. Diabetes and cardiovascular disease were also significantly correlated, but the correlation was statistically significant at the 0.05 level. Conclusion: This study demonstrates a significant overlap between sleep apnea and depression. Health specialists need more information about screening for patients with OSA to ensure proper diagnosis and treatment of those with the condition.